Effects of massage on muscle soreness and parameters associated with muscle damage following eccentric exercise of the elbow flexors - Zainuddin, Zainal Abidin; Ibrahim, Halijah; Mohd. Hashim, Asha Hasnimy (2006)
While underlying mechanism of delayed onset muscle soreness (DOMS) remains unclear, massage is widely used as a therapeutic modality for alleviating its symptom. Although a number of studies have evaluated the efficiency of therapeutic massage in DOMS, the large variability in responses between individuals to the effects of eccentric exercise has made comparison with control conditions difficult. In this study, we used an arm to arm comparison model to account for individual variability in responses. Ten healthy subjects performed 10 sets of 6 eccentric isokinetic muscle actions (90ï‚°/s) on the Cybex 6000 by each arm separated by 2 weeks. One arm received 10 minutes sports massage 3 hours after eccentric exercise, and the control arm had no treatment. Changes in indirect markers of muscle damage and DOMS (visual analogue scale: 0=no pain, 100=extremely painful) were compared between massage and control arms by a repeated measures ANOVA or a paired t test. Eccentric exercise resulted in a large strength loss (ï‚»50%), reduced range of motion (ï‚»15ï‚°), increased upper arm circumference (10 mm), elevated creatine kinase (CK) activity, and development of DOMS. DOMS was significantly (p<0.05) lower for the massage versus control condition for peak soreness of extending (42.9 vs 52.8 mm) and palpating the brachioradialis (33.0 vs 51.6). Soreness while flexing the elbow joint (25.1 vs 42.1, p=0.07) and palpating the brachialis (35.0 vs 46.7, p=0.06) was also lower with massage. No significant effects of massage on other markers were evident except CK, which showed significantly (p<0.05) lower peak at 4 days post-exercise for massage (981 IU/L) compared to control condition (2,705 IU/L). It was concluded that massage is effective in alleviating DOMS approximately 30% with minimum effects on muscle function and swelling.